Diazotrophic bacteria with activity promoting vegetable growth in Daucus carota L. (2018)
This study aimed at isolating diazotrophic bacteria with promoting activity of vegetal growth, associated to carrot culture. Samples were taken at 30, 60 and 115 days in a farm located in a rural area of the municipality of Manizales (Caldas). The diazotrophic bacteria were isolated in semi-solid culture media free of nitrogen. We described the macro and microscopic features of the obtained isolations, and identified them biochemically and molecularly. In addition, we evaluated indole compounds, nitrogenase activity and solubilization of phosphates. Gluconacetobacter diazotrophicus ATCC 49037 was used as a standard strain. We recovered 20 isolates associated to rhizosphere and 12 to rhizoplane. The molecular identification showed the presence of five genera: Rhizobium, Achromobacter, Bacillus, Enterobacter, and Stenotrophomonas. The production of indole compounds presented concentrations between 9.73 and 112.8 μg/mL. The standard strain showed a higher activity, with an indolic compound production of 172.5 μg/mL. Regarding nitrogenase activity, the isolates GIBI411, 394 and 399 had an activity greater or similar to the standard strain. The most efficient isolates in the solubilization of tricalcium phosphate were GIBI378 and 385. The solubilization of aluminum phosphate was assessed by the acid production index, with the isolates GIBI378, 391, 387 and 388 presenting the best behavior. The isolates found are potential candidates for the development of novel biotechnological processes to produce new alternative biofertilizers, considering the significant plant-growth promotion properties determined in this work.